184k views
0 votes
I need help asap please ​

I need help asap please ​-example-1
User Cgokmen
by
5.5k points

2 Answers

4 votes

Answer:

:Option C J'(-3, 4), N'(1, 4), M'(1, 1), P'(-2, -1)

Explanation:

My pleasure to help people

User Puffin
by
5.2k points
5 votes

Answer:Option C J'(-3, 4), N'(1, 4), M'(1, 1), P'(-2, -1)

Explanation:

we know that

The rule of the translation is

(x,y) -----> (x-4,y+4)

That means ----> The translation is 4 units at left and 4 units up

Find out the coordinates of the pre-image

Observing the figure

J(1,0),N(5,0),M(5,-3),P(2,-5)

Find out the coordinates of the image

Applying the rule of the translation at the coordinates of pre-image

J(1,0) -----> J'(1-4,0+4)

J(1,0) -----> J'(-3,4)

N(5,0) ---> N'(5-4,0+4)

N(5,0) ---> N'(1,4)

M(5,-3)----> M'(5-4,-3+4)

M(5,-3)----> M'(1,1)

P(2,-5) ----> P'(2-4,-5+4)

P(2,-5) ----> P'(-2,-1)

therefore

The coordinates of the image (after the transformation) are

J'(-3, 4), N'(1, 4), M'(1, 1), P'(-2, -1)